1999
DOI: 10.1007/s004200050344
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of pain drawings in the neck-shoulder region among the working population

Abstract: Pain drawings of neck and shoulder symptoms among the middle-aged general working population most usually focused on the neck-shoulder angles with a symmetrical left-right distribution. The number of separate symptom loci and their total area, left-right distribution, and symmetry were characteristics associated with symptom chronicity and severity or signs of tenderness in the neck-trapezius region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…The results are in accordance with recent reports by EctorAndersen et al [10] and Tomingas [53], who reported that increasing intensity of pain was associated with larger areas on the pain drawing in shoulder-neck complaints. Psychological distress has earlier been shown to be associated with both qualitative [3,6,24,31,45,48,59] and quantitative [33,54] evaluation of pain-drawings.…”
Section: Discussionsupporting
confidence: 83%
“…The results are in accordance with recent reports by EctorAndersen et al [10] and Tomingas [53], who reported that increasing intensity of pain was associated with larger areas on the pain drawing in shoulder-neck complaints. Psychological distress has earlier been shown to be associated with both qualitative [3,6,24,31,45,48,59] and quantitative [33,54] evaluation of pain-drawings.…”
Section: Discussionsupporting
confidence: 83%
“…This experimentally induced distribution of referred pain areas resembles the pain drawings of work-related neck and shoulder musculoskeletal disorders among the middle-aged general working population, who report pain at the neck-shoulder angles with a symmetrical left-right distribution. 3,4 The words most frequently chosen by the volunteers in this study were ''pressing,'' ''taut,'' ''sore,'' ''drilling,'' and ''spreading'' and are similar to those reported in previous studies with acute or chronic pain conditions. 3,25 Thus, the experimental model employed in the current study can reproduce acutely many of the same pain characteristics that are observed in patients complaining of work-related chronic neck-shoulder pain.…”
Section: Saline-induced Local and Referred Pain Patternmentioning
confidence: 91%
“…1,2 Moreover, the middle-aged general working population report local and referred pain at the neck-shoulder angles with a symmetrical left-right distribution. 3,4 However, most previous experimental studies related to the mechanisms of muscle pain have employed single or repeated injections of hypertonic saline 5 rather than bilateral injections, which might not exactly mirror the cutaneous and muscular sensitivity changes in chronic trapezius myalgia with bilateral pain. Bilateral injections possess, to some extent, the characteristics of multiple injections or electrical stimulations that induce central hyperexcitability, 6 spatial, 7,8 and temporal summation of pain intensity.…”
mentioning
confidence: 99%
“…The patients' neck pain history and the distribution of their pain mostly on the neck-shoulder angle and in the occipital region resembled those of the original tension neck patients of Valtonen 6 and the large population sample of neck shoulder pain patients of Toomingas. 22 Reported numbness of the upper extremities was common, although no patients with radicular findings in the clinical examination were recruited. Concomitant headache was equally common as in the musculoskeletal pain patients in a Norwegian study of Hagen et al 23 With only 5 (28%) of 18 of the untreated patients reporting improvement after 1 year and a mean improvement of Million index by 10%, they appeared to have worse than average prognosis compared to the patients reviewed by Borghouts et al 8 The number of patients who had consulted a folk healer before the study was high, but probably typical in the area, because earlier surveys have revealed figures of the same order: 55% of all adults in the area 24 and 75% of a back pain patient population 17 had consulted a folk healer, most often a bone setter, during their lifetime.…”
Section: Discussionmentioning
confidence: 99%